2022
DOI: 10.1002/ijc.34327
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for active surveillance vs standard surgery after neoadjuvant chemoradiotherapy in oesophageal cancer treatment: The NOSANO‐study

Abstract: Active surveillance may be a safe and effective treatment in oesophageal cancer patients with a clinically complete response after neoadjuvant chemoradiotherapy (nCRT). In the NOSANO-study we gained insight in patients' motive to opt for either an experimental treatment called active surveillance or for standard immediate surgery. Both qualitative and quantitative analyses methods were used. Forty patients were interviewed about their treatment preference, 3 months after completion of nCRT (T1). Data were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…A recently published study from our group suggests that the patients' interpretation of the doctor's advice can influence their treatment preferences. [33] It was found that if a doctor seems -according to the patiententhusiastic about one of both treatment options, the patient is tended to opt for that specific treatment, independent of whether that treatment is active surveillance or surgery. It should however be noted that the patients that participated in this study had a strong preferences for one of the two treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study from our group suggests that the patients' interpretation of the doctor's advice can influence their treatment preferences. [33] It was found that if a doctor seems -according to the patiententhusiastic about one of both treatment options, the patient is tended to opt for that specific treatment, independent of whether that treatment is active surveillance or surgery. It should however be noted that the patients that participated in this study had a strong preferences for one of the two treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…This was clearly demonstrated by another study from our group, where we found that several patients with a complete clinical response after nCRT worded their motivation for active surveillance treatment as “I feel all good right now, I trust my body, why would I undergo surgery“; and some patients opting for surgery motivated their choice with “I know it may not be necessary to undergo surgery, but I would not forgive myself if I did not do everything that may possibly help”, indicating anticipated regrets. 23 So, in short, the final outcome (i.e., treatment choice) then is the result of a subjective evaluation of multiple factors. As this can be quite complex, presuming that “just providing the facts” will lead to an well‐considered treatment choice is obsolete.…”
Section: Discussionmentioning
confidence: 99%